Can salivary testosterone and cortisol reactivity to a mid-week stress test discriminate a match outcome during international rugby union competition? - Crewther, B. T.; Potts, N.; Kilduff, L. P.; Drawer, S.; Cook, C. J. (Journal of Science and Medicine in Sport, 2018)
Objectives: Evidence suggests that stress-induced changes in testosterone and cortisol are related to future competitive behaviours and team-sport outcomes. Therefore, we examined whether salivary testosterone and cortisol reactivity to a mid-week stress test can discriminate a match outcome in international rugby union competition. Design: Single group, quasi-experimental design with repeated measures. Method: Thirty-three male rugby players completed a standardised stress test three or four days before seven international matches. Stress testing involved seven minutes of shuttle runs (2 × 20 m), dispersed across one-minute stages with increasing speeds. Salivary testosterone and cortisol were measured in the morning, along with delta changes from morning to pre-test (Morn-Pre delta) and pre-test to post-test (Pre-Post delta). Data were compared across wins (n = 3) and losses (n = 4). Results: The Morn-Pre delta in cortisol increased before winning and decreased prior to losing (p < 0.001), with a large effect size difference (d = 1.6, 90% CI 1.3-1.9). Testosterone decreased significantly across the same period, irrespective of the match outcome. The Morn-Pre delta in testosterone and cortisol, plus the Pre-Post delta in testosterone, all predicted a match outcome (p = 0.01). The final model showed good diagnostic accuracy (72%) with cortisol as the main contributor. Conclusions: The salivary testosterone and cortisol responses to mid-week testing showed an ability to discriminate a rugby match outcome over a limited number of games. The Morn-Pre? in cortisol was the strongest diagnostic biomarker. This model may provide a unique format to assess team readiness or recovery between competitions, especially with the emergence of rapid hormonal testing.